Is there a role of iNOS activation in the delayed antiarrhythmic effect of sodium nitrite? - Demeter-Haludka Vivien; Juhász László; Kovács Mária; Gardi János; Végh Ágnes (2016)
This study aimed to examine whether inducible nitric oxide synthase (iNOS) plays a role in the delayed antiarrhythmic effect of sodium nitrite. Twenty-one dogs were infused intravenously with sodium nitrite (0.2 micromol/kg/min) for 20 min, either in the absence (n=12) or in the presence of the iNOS inhibitor S-(2-aminoethyl)-isothiourea (AEST; total dose: 2.0 mg/kg; i.v., n=9). Control dogs (n=12) were given saline. Twenty-four hours later, all the dogs were subjected to a 25 min period occlusion of the left anterior descending (LAD) coronary artery, followed by rapid reperfusion. Dogs treated with AEST and nitrite were received again AEST prior to the occlusion. Compared to the controls, sodium nitrite markedly reduced the number of ectopic beats, the number and incidence of ventricular tachycardia and the incidence of ventricular fibrillation during occlusion and increased survival (0% vs. 50%) from the combined ischaemia and reperfusion insult. Although AEST completely inhibited iNOS activity, the nitrite induced increased NO bioavailability during occlusion was not substantially modified. Furthermore, AEST attenuated but did not completely abolish the antiarrhythmic effect of nitrite. The marked delayed antiarrhythmic effect of sodium nitrite is not entirely due to the activation of iNOS; other mechanisms may certainly play a role.